Produção de Mudas de Ipê-amarelo (Tabebuia serratifolia) em resposta a fertilização nitrogenada - Goulart, Lívia Mara Lima [UNESP]; de Paiva, Haroldo Nogueira; Leite, Hélio Garcia; Xavier, Aloisio; Duarte, Marciel Lelis (FapUNIFESP (SciELO), 2017)
This work aimed to evaluate the effect of sources of nitrogen and respective levels on growth and quality of Yellow Cortez (Tabebuia serratifolia) seedlings. Seedlings were grown on a Oxisol and nitrogen sources were ammonium nitrate, ammonium sulphate and calcium nitrate, applied in five doses (0, 75, 150, 225 and 300 mg dm-3) and increments of 25, 50, 75 and 100 days after transplanting. The experimental design was randomized in blocks in factorial scheme (3 × 5) with four replications. At 125 days after transplanting, the addition of nitrogen provided significant effect on seedling production of Yellow Cortez (Tabebuia serratifolia), and the ammonium sulfate produced the best means for all traits and indexes evaluated. We recommend the use of ammonium sulfate at a dose of 100 mg dm-3 N for Yellow Cortez seedling.
Production of Yellow Cortez (Tabebuia serratifolia) seedlings in response to nitrogen fertilization
Keywords: Forest nutrition; Native species; Nitrogen; Plant propagation